2017
DOI: 10.3390/rs9040367
|View full text |Cite
|
Sign up to set email alerts
|

Turbidity in Apalachicola Bay, Florida from Landsat 5 TM and Field Data: Seasonal Patterns and Response to Extreme Events

Abstract: Synoptic monitoring of estuaries, some of the most bio-diverse and productive environments on Earth, is essential to study small-scale water dynamics and its role on spatiotemporal variation in water quality important to indigenous marine species and surrounding human settlements. We present a detailed study of turbidity, an optical index of water quality, in Apalachicola Bay, Florida (USA) using historical in situ measurements and Landsat 5 TM data archive acquired from 2004 to 2011. Data mining techniques su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 69 publications
(53 reference statements)
1
20
0
1
Order By: Relevance
“…Joshi et al [39], for example, found that turbidity in Apalachicola Bay, Florida, (located approximately 300 km from Mobile Bay to the west and Tampa Bay to the southeast) is largely driven by a combination of river discharge, wind speed, tides and precipitation, and that the interactions of these physical forcings affect different sections of the bay in dynamic ways. We found that Mobile Bay turbidity is driven by a combination of river discharge, wind speed, water level and precipitation, and that the three Florida estuaries (TB, CH, SB) are driven by wind speed and discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joshi et al [39], for example, found that turbidity in Apalachicola Bay, Florida, (located approximately 300 km from Mobile Bay to the west and Tampa Bay to the southeast) is largely driven by a combination of river discharge, wind speed, tides and precipitation, and that the interactions of these physical forcings affect different sections of the bay in dynamic ways. We found that Mobile Bay turbidity is driven by a combination of river discharge, wind speed, water level and precipitation, and that the three Florida estuaries (TB, CH, SB) are driven by wind speed and discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In general, we assumed that MODIS Band 1 observations have minimal contributions from light reflected from the sea bottom in estuarine waters deeper than about 2.8 m due to the strong absorption of red light by water [21]. This approach has been used several times in the past, with mixed success, in different estuaries and coastal waters around the world [6,13,14,21,[33][34][35][36][37][38][39]. Other bio-optical algorithms that utilize blue, green, or yellow bands to estimate parameters such as chlorophyll-a concentration are usually contaminated by reflectance from the ocean bottom in shallow areas and don't provide accurate estimates.…”
Section: Turbidity Proxymentioning
confidence: 99%
“…In recent years, both empirical and semi-analytical models have been frequently used to link satellite observations and in-water properties, such as IOPs, vertical diffuse attenuation coefficients (K d ), suspended particulate matter (SPM) concentrations, CDOM, pigment concentrations, phytoplankton cell counts and cell size, and particle size (D'Sa et al, 2003(D'Sa et al, , 2007Pan et al, 2010;Chen et al, 2013;Brewin et al, 2015;Joshi et al, 2017b). Empirical relationships are mathematical formulations (e.g., simple or multiple regressions) that directly link water-leaving measurements to the parameter of interest in surface waters.…”
Section: Introductionmentioning
confidence: 99%
“…Turbidity climatology over an eight-year period (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) in Apalachicola Bay was investigated based on remote sensing estimation from Landsat 5 TM and Landsat 8 OLI imagery using a single-band empirical relationship of band 3 [22]. Deng et al [23] tested the applicability of the Vertically Generalised Production Model (VGPM) to estimate phytoplankton primary production by comparing the model-derived and the in situ results, investigated the long-term temporal-spatial variations in primary production using MODIS data, and further discussed the potential affecting factors in Lake Taihu.…”
Section: Highlights Of Research Articlesmentioning
confidence: 99%